Dental Sleep Medicine Education Amongst Accredited Orthodontic Programmes in Thailand - Supakit Peanchitlertkajorn; Premthip Chalidapongse; Thanyaluck Jiansuwannapas; Nattaporn Surinsirirat; Patipan Khamphuang; Paweelada Boonyai; Kawin Sipiyaruk (Elsevier, 2024)
ABSTRACT: Background: Dental sleep medicine education (DSME) should be emphasised in postgraduate orthodontic training; however, there appears to be no clear guideline for its implementation into the curriculum. Objective: The aim was to investigate the current status of DSME as well as its feasibility and implementation in postgraduate orthodontic programmes. Methods: A structured interview with predetermined response options was chosen as a data collection method to gather relevant information from representatives of all accredited postgraduate orthodontic programmes in Thailand. These interviews were conducted online via the Cisco Webex Meeting platform. A combination of data analysis techniques was employed to achieve a thorough comprehension of the research findings, including descriptive statistics, quantitative content analysis, thematic analysis, and alignment analysis. Results: All participating programmes reported the inclusion of DSME in their curricula. A didactic approach was adopted by all programmes. However, only 2 out of 7 programmes offered clinical sessions for their students. Several challenges in implementing DSME within orthodontic programmes were identified, including a shortage of expertise and limited patient access. The participants also suggested that knowledge and resource sharing amongst institutions could serve as a potential solution to enhance the feasibility of DSME. Conclusions: This research highlighted the significant disparities and inadequacy of DSME within postgraduate orthodontic programmes in Thailand due to various challenges. Consequently, there is a compelling need to place greater emphasis on DSME and establish a national-level standardisation within orthodontic programmes. This effort is essential for enhancing the awareness and competency of orthodontists in the field of DSME.